1987
DOI: 10.1007/bf02098500
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of haloperidol, clozapine, and fluperlapine on tuberoinfundibular dopamine neurons and prolactin secretion in the rat

Abstract: Two atypical neuroleptic agents, clozapine and fluperlapine, produced rapid elevations in plasma PRL concentrations that were similar in magnitude to those produced by haloperidol. However, the PRL response to clozapine or fluperlapine was of much shorter duration than that elicited by haloperidol. Clozapine, but neither fluperlapine nor haloperidol, produced a rapid increase in the activity of tuberoinfundibular dopamine (TIDA) neurons, as evidenced by an enhanced accumulation of dihydroxyphenylalanine (DOPA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

1989
1989
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 37 publications
1
19
0
1
Order By: Relevance
“…Clozapine did not increase plasma prolactin levels in our adolescent sample during maintenance treatment, consistent with clinical data and animal studies (Ackenheil 1989, Albinsson et al 1993, Gudelsky et al 1987, Lieberman et al 1986, Meltzer 1989, 1992b. Basal prolactin secretion is under inhibitory dopaminergic control but is stimulated by serotonin agonists (Meltzer 1992a,b).…”
Section: Prolactin Levelssupporting
confidence: 89%
“…Clozapine did not increase plasma prolactin levels in our adolescent sample during maintenance treatment, consistent with clinical data and animal studies (Ackenheil 1989, Albinsson et al 1993, Gudelsky et al 1987, Lieberman et al 1986, Meltzer 1989, 1992b. Basal prolactin secretion is under inhibitory dopaminergic control but is stimulated by serotonin agonists (Meltzer 1992a,b).…”
Section: Prolactin Levelssupporting
confidence: 89%
“…Clinically, several studies have demonstrated elevations of prolactin on initial treatment with antipsychotics (Hamner 2002;Crawford et al 1997;Goff et al 1998;Gudelsky et al 1987). Olanzapine was found to produce moderate increases in prolactin levels in the acute phase of treatment (6 weeks), whilst risperidone has been associated with 30-300% increases over the same period (Breier et al 1999;David et al 2000).…”
Section: Discussionmentioning
confidence: 96%
“…This shortlasting increase of prolactin is most probably a result of the ability of the atypical antipsychotics to stimulate the TIDA neurons [Gudelsky et al, 19871. In contrast typical antipsychotic drugs do not influence the activity in the TIDA neurons [Gudelsky et al, 1987;Gudelsky and Meltzer, 19891. Atypical antipsychotics are more potent stimulators of the hypothalamic-pituitary-adrenocortical axis than typical antipsychotic drugs because of an elevated serotonergic nerve activity induced by the atypical ones "ash et al, 19881.…”
Section: Plotmentioning
confidence: 98%